Kajian Keterikatan Tempat di Daerah Perkotaan (Studi Kasus: Kelurahan Gabahan dan Kelurahan Jabungan Semarang) - Azahro, Mustovia (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Place attachment is social-phsycological effect which is formed by interpreting the place. In urban area, place attachment fades away because there are many non-natives live in urban area. Even in uban kampong which its community has close-knit interaction, attachment to place fades because non-natives have lower level of attachment to new dwelling place. However, natives ofurban kampong located in city center still have high level of attachment. Nonetheless, attachment to place of natives who live in city center is higher than natives who live in suburban. It provides an explanation that natives who live in suburban have lower level of dependence to their place. Natives wholive in city center with middle-low economy have high level of place attachment whereas with middle-high economy have lower attachment, and then natives who live in city center with middle-high economy have tendency to live in another more secure and comfortable dwelling place. Security and comfort is the most influence factor of place attachment in both natives who live in city center and suburban. This research is implemented in Kelurahan Gabahan as kampong in city center and Kelurahan Jabungan as kampong in suburban.